Electrochemical sensing and photocatalytic degradation of methylene blue (MB) dye by cobalt-beta hydroxy benzoate complex. (October 2019) - Sangeetha, S.; Krishnamurthy, G.; Raghavan, M. Srinidhi
Abstract: In this work describes the cobalt-beta hydroxyl benzoate (Co-bhb), Cobalt based complex has been synthesized by solvothermal method and verified for the application detection and removal of environmentally hazardous molecule like methylene blue. The Co-bhb sample were characterized by various techniques like FTIR, PXRD, MS-Mass analysis, NMR, and SEM, EDX, ES-TEM, XPS, PL and BET surface area measurement. The Co-bhb/cp electrode was prepared and electrochemical performance was carried out to explore the electrical activity of the complex for dye sensor application. The Cyclic voltammetry studies were made in 0.05M K4 Fe (CN)6 solution and electrochemical sensing experiments were performed in 0.05M H2 SO4 . An excellent response resulted of the Co-bhb/cpe for sensing the dye at very low concentrations. In addition the photocatalytic activity of degradation of Methylene blue has been performed. The results have showed that the Co-bhb is a promising candidate for electrochemical and catalytic properties. Highlights: Solvothermal route synthesis of Co-bhb complex. Transmission Microscopy revealed nearly 2–5 nm of cobalt nanoparticles resulted. A detailed electrochemical behavior and photocatalytic activity of cobalt complex is explored. High response sensor and repeatability Co-bhb has been reported.